Incidence and Associated Risk Factors of Contrast Induced Nephropathy in Diabetes and Non Diabetic Patients (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Contrast-induced nephropathy (CIN) is the third leading cause of hospital-acquired acute renal failure.Objective: The purpose of the present study was to compare the incidence and associated risk factors of contrast induced nephropathy in diabetes and non-diabetic patients.Methodology: This was cross-sectional study performed in the Department of Nephrology at National Institute of Kidney Diseases and Urology, Sher-E-Bangla Nagar, Dhaka and Department of Cardiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh from January 2016 to July 2016. Contrast induced nephropathy (CIN) is defined as increase in serum creatinine of ≥25% from baseline value and/ or an absolute increase of ≥0.5 mg/dl in serum creatinine from baseline. Patients were divided in to two groups Group A (Patients with Diabetes mellitus) and Group B (Patients without Diabetes mellitus). To identify independent characteristics associated with CIN, multivariable logistic regression analysis was used through SPSS version 23. Results of this model were presented as Odds Ratio (OR). P value was calculated to see the significance of various risk factors in diabetes and non-diabetes patients.Results: The difference in baseline creatinine serum creatinine was found statistically significant (P